Schisandrin B attenuates CCl4-induced liver fibrosis in rats by regulation of Nrf2-ARE and TGF-β/Smad signaling pathways - Chen QS; Zhang H; Cao Y; Li Y; Sun S; Zhang JP; Zhang GQ (Dove Medical Press, 2017)
Qingshan Chen,1,* Hai Zhang,2,* Yan Cao,3 Ying Li,1 Sen Sun,1 Junping Zhang,4 Guoqing Zhang1 1Department of Pharmacy, Shanghai Eastern Hepatobiliary Surgery Hospital, Second Military Medical University, Shanghai, China, 2Department of Pharmacy, Shanghai First Maternity and Infant Hospital, Tongji University School of Medicine, Shanghai, China, 3Department of Biochemical Pharmacy, College of Pharmacy, Second Military Medical University, Shanghai, China; 4Department of Biochemical Pharmacy, College of Pharmacy, Second Military Medical University, Shanghai, China *These authors contributed equally to this work Abstract: Liver fibrosis is a major pathological feature of chronic liver diseases and there is no effective therapy program at present. Schisandrin B (Sch B) is the major bioactive ingredient of Schisandra chinensis, with antioxidative, anti-inflammatory, antitumor, and hepatoprotective properties. This study aimed to investigate the protective effect and related molecular mechanism of Sch B against carbon tetrachloride (CCl4)-induced liver fibrosis in rats. The in vivo therapeutic effect of Sch B on liver fibrosis induced by CCl4 was examined in rats. In vitro, rat hepatic stellate cells (HSC-T6) were used to assess the effect of Sch B on the activation of HSCs. Sch B effectively attenuated liver damage and progression of liver fibrosis in rats, as evidenced by improved liver function and decreased collagen deposition. The effects of Sch B were associated with attenuating oxidative stress by activating nuclear factor-erythroid 2-related factor 2 (Nrf2)-mediated antioxidant signaling and suppressing HSC activation by inhibiting the transforming growth factor-β (TGF-β)/Smad signaling pathway. In an in vitro study, it was shown that Sch B inhibited TGF-β-induced HSC activation. Finally, Sch B significantly inhibited TGF-β1-stimulated phosphorylation of Smad and signaling of mitogen-activated protein kinases. This study demonstrates that Sch B prevents the progression of liver fibrosis by the regulation of Nrf2-ARE and TGF-β/Smad signaling pathways, and indicates that Sch B can be used for the treatment of liver fibrosis. Keywords: schisandrin B, liver fibrosis, hepatic stellate cell activation, Nrf2, TGF-β/Smad